1983
DOI: 10.1113/jphysiol.1983.sp014643
|View full text |Cite
|
Sign up to set email alerts
|

Receptive field organization and response properties of spinal neurones with axons ascending the dorsal columns in the cat.

Abstract: SUMMARY1. Micro-electrode recordings were made from single post-synaptic axons in the dorsal columns of cats anaesthetized with chloralose and paralysed with gallamine triethiodide. The recordings were made from the L5 segment and the axons were shown to project to the upper cervical level.2. Forty-eight units were recorded and the axons had conduction velocities of 22-61 ms-1, averaging 38-3 ms-1.3. Excitatory receptive fields were complex in many units, being made up of clearly defined, separate, low and hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

1988
1988
2002
2002

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 28 publications
3
25
0
Order By: Relevance
“…While a small minority of units with spatially separate excitatory fields has been previously reported among samples of unidentified dorsal horn neurones (Devor & Wall, 1976;Pubols & Goldberger, 1980;Brenowitz & Pubols, 1981) these have always been located on the most proximal areas of the limb. Indeed, apart from previous studies of this system in the chloralose-anaesthetized cat (Brown & Fyffe, 1981;Brown et al 1983), there are no reports of dorsal horn neurones with complex receptive fields of the type that have been observed for PSDC units with input from glabrous skin. Several previous studies of PSDC neurones in the pentobarbitone-anaesthetized cat have failed to detect inhibitory input (Uddenberg, 1968;Angaut-Petit, 1975;Lu et al 1983), but inhibitory fields have been reported in about half of a sample of PSDC neurones recorded in the chloralose-anaesthetized cat (Brown et al 1983).…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…While a small minority of units with spatially separate excitatory fields has been previously reported among samples of unidentified dorsal horn neurones (Devor & Wall, 1976;Pubols & Goldberger, 1980;Brenowitz & Pubols, 1981) these have always been located on the most proximal areas of the limb. Indeed, apart from previous studies of this system in the chloralose-anaesthetized cat (Brown & Fyffe, 1981;Brown et al 1983), there are no reports of dorsal horn neurones with complex receptive fields of the type that have been observed for PSDC units with input from glabrous skin. Several previous studies of PSDC neurones in the pentobarbitone-anaesthetized cat have failed to detect inhibitory input (Uddenberg, 1968;Angaut-Petit, 1975;Lu et al 1983), but inhibitory fields have been reported in about half of a sample of PSDC neurones recorded in the chloralose-anaesthetized cat (Brown et al 1983).…”
Section: Discussionmentioning
confidence: 92%
“…Indeed, apart from previous studies of this system in the chloralose-anaesthetized cat (Brown & Fyffe, 1981;Brown et al 1983), there are no reports of dorsal horn neurones with complex receptive fields of the type that have been observed for PSDC units with input from glabrous skin. Several previous studies of PSDC neurones in the pentobarbitone-anaesthetized cat have failed to detect inhibitory input (Uddenberg, 1968;Angaut-Petit, 1975;Lu et al 1983), but inhibitory fields have been reported in about half of a sample of PSDC neurones recorded in the chloralose-anaesthetized cat (Brown et al 1983). The present results confirm that a large proportion (75 %) of PSDC neurones, at least in the chloralose-anaesthetized cat, have inhibitory receptive fields on the ipsilateral limb.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations